The Semantic Organization knowing what you know. - Wacey, Michael
Corporations have a tremendous amount of stored information. On top of this, new information is being created every day. A small but critical portion of this information is stored in highly structured and well-defined formats in relational databases. However, most of the information is on paper, in e-mail, in word processing documents, in spreadsheets, in PDF files, in engineering diagrams and so on.